Approach of the Interaction Enzyme-Substrate by Molecular Modelling - SARI, S.; MEDJAHED, W.; KAJIMA MULENGI, J.; GHALEM, S. (Asian Journal of Chemistry, 2010)
In the biological systems, the chemical reactions of the metabolism proceed seldom spontaneously, but they are generally catalysed by particular proteins which one calls enzymes. Whole of these biological functions pass by a reaction of complexation while utilizing certain atoms belonging to a given number of amino acids representing the active site. On the level of this active site, the behaviour of the atoms is relatively different as for the approach from the enzyme and the substrate. At the time of this approach, there are interactions enzyme-substrate which control the stability of a E-S complex leading to the end product according to the specificity of the enzyme. It is on this level that resides the difficulties of comprehension of the interactions between enzyme and substrate. On the basis of this idea we propose to elucidate this mechanism by molecular modelling. We are particularly interested in studying the interaction of the phospholipase A2 (PLA2) with aziridines structures by molecular modelling and molecular dynamics.